Enhancing professional skills of prospective teachers in Kazakhstan through digital technologies - Assylbayeva, Zheniskul; Nurzhanova, Sazhila; Kurman, Nessibeli; Yessim, Ulzhalgas; Kudaibergenova, Maira (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study’s relevance stems from the increasing integration of digital technologies (DT) in education and the growing need for future educators to develop digital competencies. As teaching methods evolve to incorporate innovative tools, understanding how DT can effectively enhance professional skills (PS) is critical for preparing prospective teachers to meet the demands of 21st-century classrooms. This study aims to investigate digital technology’s effectiveness in enhancing prospective teachers’ PS. The research sample comprised 178 prospective teachers from the Abai Kazakh National Pedagogical University. Participants in the digital training constituted the sample of prospective teachers in the experimental group (EG). The results’ correlation shows that the groups’ indicators before and after the digital training differed significantly. The beneficial dynamics of dependent variables brought about by the digital training attest to the efficacy of the current pedagogical support in terms of enhancing the PS of teacher candidates. Given the country’s ongoing educational reforms and efforts to modernize the system, this study fills a crucial gap by providing region-specific insights and offering practical insights for enhancing the PS of prospective teachers, which can be applied in pedagogical universities. These findings help to bridge the theory-practice gap by investigating the practical applications of digital tools in skill development.